Study of prevalence of bacterial vaginosis in preterm and term labour - Masand, Deepa; Melkani, Deepshikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of the study was to study the prevalence of bacterial vaginosis in women with preterm & term labour & to analyze the causal relationship of bacterial vaginosis with preterm labour. Methods: An observational study conducted on 100 patients reporting at labour room in Obstetrics & Gynaecology department of NIMS Medical College & hospital, between November 2013 to June 2014 involving 50 patients with preterm & 50 with term labour. Results: Patients who fulfilled Amsel’s criteria and patients with discharge suggestive of bacterial vaginosis were significantly more in preterm labour group as compared to term labour group. Out of 50 patients in preterm labour group, 18(36%) were suggestive of bacterial vaginosis, 32(64%) were not suggestive of bacterial vaginosis. Out of 50 patients in term labour group, 4(8%) were suggestive of bacterial vaginosis, 46(92%) were not suggestive of bacterial vaginosis. Conclusions: Bacterial vaginosis is major risk factor for preterm labour. Therefore, testing for bacterial vaginosis & prompt treatment may reduce risk of preterm labour.